The basic laws of human stupidity - Cipolla, Carlo M.; Taleb, Nassim Nicholas, 1960- (London : WH Allen, 2019)
"An economist explores the five laws that confirm our worst fears: stupid people can and do rule the world"-- Provided by publisher.
The first basic law -- The second basic law -- A technical interlude -- The third (and golden) basic law -- Frequency distribution -- Stupidity and power -- The power of stupidity -- The fourth basic law -- Macro analysis and the fifth basic law.
Translation of: Leggi fondamentali della stupidita umana.
"The Basic Laws of Human Stupidity was originally published in Italian in 1988 by Societa editrice il Mulino. First published in English by Societa editrice il Mulino. c2011 by Societa editrice il Mulino, Bologna."
Keywords: Stupidity -- Humor; Conduct of life -- Humor